Short communication. Effect of enzyme addition on the nutritive value of six lupin cultivars with different alkaloid content - Brenes, A.=700 1 Marquardt, R.R.; Muzquiz, M.; Guenter, W.; Viveros, A.
(Es, En)
ilus., 29 ref.
Keywords: ALIMENTACION DE LOS ANIMALES; AVES DE CORRAL; POLLO; ALCALOIDES; LUPINUS ALBUS; VALOR NUTRITIVO; PRODUCCION; ESPAÑA; ALTRAMUZ